COPYRIGHT PROTECTION OF SONG WORKS DIGITALIZED THROUGH THE INTERNET - Budimah Budimah; Moh Nafri (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The purpose of this research is to find out and analyze the application of copyright protection to songs that are digitized based on Law Number 28 of 2014 concerning Copyrights. The research method uses normative legal research that uses primary and secondary legal materials. The processing of legal materials is basically a series of activities to systematize or classify written legal materials to facilitate the analysis of primary legal materials. The results of the study found that technology protection for digital creations is an important thing, as an effort to protect digital creations from acts of copyright infringement. Copyright is a part of intellectual property rights. The concept of copyright protection itself concerns: in the form of what objects are protected, how the protection occurs, and the extent to which the protection is given. Suggestions for research The government should conduct socialization, by inculcating habits to the wider community to understand the existing norms. The socialization is nothing but to raise public awareness that uploading a file that is at work on the internet without permission is not justified and violates the law.